Keratitis (IntechOpen, 2024)
Keratitis is one of the leading causes of blindness worldwide. In most cases, corneal diseases are preventable or treatable; thus, a comprehensive knowledge of epidemiology, causes, diagnosis, and treatment of the multiple forms of keratitis is crucial in clinical practice. This provides a comprehensive overview of keratitis, including information on current ocular diagnostic methods and their theoretical basis, practical approach, and usage in clinical practice. It also highlights recent advances in the methods of treating keratitis.